GENERAL DESIGN ALGORITHM BASED ON PSEUDO-EQUILIBRIUM CONCEPT FOR MULTISTAGE MULTI-COMPONENT LIQUID-LIQUID SEPARATION PROCESSES - TSUBOKA, TAKESHI; KATAYAMA, TAKASHI (JOURNAL OF CHEMICAL ENGINEERING OF JAPAN, 1976)
A new general method for mathematical simulation of multicomponent equilibrium stage processes is presented. The procedure consists of solving component material balance equations with a tridiagonal matrix algorithm and performing equilibrium calculation based on the "pseudoequilibrium" concept, instead of solving simultaneous equilibrium equations by some optimization method. The present method is simple, fast and numerically stable. The application of the method to multistage, multicomponent extraction problems is described. Moreover, the feasibility of the modified Wilson equation to extraction problems is shown.